Interpretation of osmotic gradient ektacytometry (osmoscan) data: A comparative study for methodological standards. (May 2015) - Nemeth, Norbert; Kiss, Ferenc; Miszti-Blasius, Kornel
Abstract Osmotic gradient ektacytometry (measuring elongation index in the function of osmolality at a constant shear stress) is a sensitive method to analyze red blood cell (RBC) deformability and investigating the optimal osmolality range for the cells in normal or pathophysiological cellular and micro-environmental conditions. However, the methodological conditions are different, since the results are influenced by the applied shear stress (SS). In this study we investigated rat, dog, pig and human blood samples at SS of 1, 2, 3, 5, 10, 20 and 30 Pa. To describe the range being related to the cell deformability, we introduced new calculated parameters obtained from the raw data of the elongation index (EI)-osmolality (O) curves. Our results showed that: (1) Osmoscan data tested at 20 or 30 Pa do not differ significantly from each other; (2) Under SS of 20 Pa the EImax, the O (EImax), the EI min and the area under curve nearly linearly decrease in the function of SS with different slope in rat, dog, pig and human blood; (3) Measurements under 3 Pa SS become unstable; (4) The differences between minimal and maximal EI and the belonging osmolality values, and their ratios, as new calculated parameters (ΔEI, ΔO, ΔEI/ΔO, EImax/EImin and O (EImax)/Omin) can be suitable for further analysis of the osmoscan curves together with other hemorheological parameters describing RBC deformability; and (5) Decreased erythrocyte deformability (by rigidifying with glutaraldehyde) can be reflected well with the following, calculated osmoscan parameters: ΔO, rO, rEI/rO and ΔEI/ΔO.